2004
DOI: 10.1196/annals.1331.021
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Respiratory Infection in the Elderly

Abstract: Respiratory infections are prevalent in the elderly, resulting in increased morbidity, mortality, and utilization of health care services. Contributing to the increased incidence of infection with age is the well-described decline in immune response, which has been correlated with patterns of illness in the elderly. For example, there are higher morbidity and mortality from cancer, pneumonia, and post-operative complications in those who have diminished, delayed-type hypersensitivity skin test responses. Nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…17, 34 Individuals with vitamin deficiencies are at increased risk for respiratory infections, 10 and vitamin supplementation has been shown to decrease the rate of respiratory infections in certain populations. [11][12][13][14][15][16][18][19][20] Micronutrients can improve cell-mediated immunity and reduce oxidative stress. 35 Vitamin E supplementation in healthy, well-nourished adults increased delayed hypersensitivity responses, response to hepatitis B vaccine, lymphocyte proliferation, and decreased formation of immunosuppressive prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 34 Individuals with vitamin deficiencies are at increased risk for respiratory infections, 10 and vitamin supplementation has been shown to decrease the rate of respiratory infections in certain populations. [11][12][13][14][15][16][18][19][20] Micronutrients can improve cell-mediated immunity and reduce oxidative stress. 35 Vitamin E supplementation in healthy, well-nourished adults increased delayed hypersensitivity responses, response to hepatitis B vaccine, lymphocyte proliferation, and decreased formation of immunosuppressive prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Other studies have found no benefit with vitamin supplementation in reducing the rate of respiratory infections. 6, 17-20 Merchant and colleagues demonstrated that vitamin E intake from food sources, but not total intake, was inversely associated with pneumonia risk in US men.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the fat-soluble vitamins A, D and E have been shown to affect immune cell lineage development, as well as several immune functions including apoptosis and phagocytosis (10) . In addition, vitamin E supplementation in the elderly has been shown to reduce susceptibility to infection (11) , and vitamin C has since 1937 been suggested to reduce the risk of URTI (12) . Other nutrients suggested to affect the risk of URTI are n-3 fatty acids, selenium and zinc (10,13,14) .…”
mentioning
confidence: 99%
“…It has been shown to be associated with immune function and resistance to infections in both animal [11] and human [12] studies. Some randomized trials with elderly participants (see [13] for a review) showed a protective effect of vitamin E supplementation against the common cold, with a RR of 0.80 (95% CI 0.64-0.98).…”
Section: Introductionmentioning
confidence: 98%
“…Most previous studies on antioxidants and URTI have studied the effect of large doses through supplement use [10,13,14]. Few studies have focused on antioxidants from food [15].…”
Section: Introductionmentioning
confidence: 99%